ASSESSING INDONESIA’S COMPLIANCE WITH INTERNATIONAL LAWS AGAINST MIGRANT SEAFARER FORCED LABOUR - Markus Andre Mefiboset Simbolon; Davina Oktivana2 (KANUN:JURNAL ILMU HUKUM, 2025)
Despite the growing global consensus and establishment of numerous public international law instruments to combat forced labour practices, Indonesian migrant seafarers continue to suffer, especially at sea. Indonesia has ratified various international conventions against forced labour, while persistent practices highlight a contradiction between its international commitments and their practical implementation. This study therefore assesses Indonesia’s compliance through the ratification of key instruments, including human rights treaties such as the International Covenant on Civil and Political Rights (ICCPR); labour standards under International Labour Organization (ILO) Conventions No. 29 and No. 188; and provisions under United Nations Convention on the Law of the Sea (UNCLOS), employing a normative judicial review approach. The analysis identifies substantive gaps in Indonesia’s national legal framework, such as the absence of a clear forced labour definition, deficient inspection mechanisms for fishing vessels, and inadequate oversight of recruitment agencies. While Indonesia possesses full legal capacity as a coastal state, these gaps hinder state duties to properly address forced labour. The study concludes that legal reformation and additional ratification of ILO Protocol No. 29 and Convention No. 188 are necessary to strengthen international cooperation and enhance protection for Indonesian migrant seafarers.